Rehabilitation management in Parkinson's disease - review of the variety of forms - Beniamin Szmelcer; Patrycja Wszelaki; Michał Wilczyński; Natalia Krakowska; Daria Zaborna; Aleksandra Fortuna; Justyna Ciepłuch; Aleksander Florczak; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2019)
Introduction: Parkinson's disease is one of the most common central nervous system diseases. Despite many studies and the use of many different forms of drug treatment, it is still not possible to completely regress the disease. Drug treatment can effectively reduce the severity of stiffness, slow motion or tremor, but does not affect non-dopaminergic symptoms such as postural and gait stability disorders which can result in numerous falls. Materials and methods: Analysis of selected and available literature and scientific articles available in the Google Scholar and Pubmed search engine database. Keywords were used for this purpose: Parkinson's disease, Rehabilitation, and Therapy Results: The most common symptoms of a neurodegenerative disease, which is Parkinson's disease, include slow motion, increased muscle tone, resting tremor, and balance disorders. The etiopathogenesis of Parkinson's disease is still not fully understood, and for this reason a simple algorithm was still created for the diagnosis of the disease and possible further treatment. Kinesitherapy, which is individually tailored to the patient's needs, is the basic form of rehabilitation in Parkinson's disease. For this purpose, muscle stretching exercises, autogenic training, exercises improving efficiency, respiratory therapy or progressive muscle relaxation by the Jacobson method are used. In the case of physical therapy, which is complementary to rehabilitation, hydrotherapy, magnetotherapy and iontophoresis are used. In addition to the above-mentioned forms of rehabilitation, deep therapeutic stimulation of the brain, subcutaneous administration of apomorphine, basic forms of occupational therapy and speech therapy exercises are also used for therapeutic purposes. Conclusions: Despite the large amount of research and published results, there is still a great need for further work on the problems of people with Parkinson's disease.